Immunogenicity and Safety of Concomitant Administration of a Combined Hepatitis A/B Vaccine and a Quadrivalent Meningococcal Conjugate Vaccine in Healthy Adults. Issue 2 (7th December 2014) - Alberer, Martin; Burchard, Gerd; Jelinek, Tomas; Reisinger, Emil C.; Meyer, Seetha; Forleo‐Neto, Eduardo; Dagnew, Alemnew F.; Arora, Ashwani Kumar
<x xml:space="preserve">Abstract</x> Background This phase 3b randomized, open‐label study evaluated the immunogenicity and safety of coadministration of a hepatitis A and/or B vaccine with a quadrivalent oligosaccharide meningococcal CRM197‐conjugate vaccine (MenACWY‐CRM), in the context of an accelerated hepatitis A and/or B immunization schedule. Methods A total of 252 healthy adult subjects were randomized to three groups to receive hepatitis A/B only (HepA/B), hepatitis A/B coadministered with MenACWY‐CRM (HepA/B+MenACWY‐CRM), or MenACWY‐CRM only (MenACWY‐CRM). Hepatitis A and/or B vaccination was administered in the form of a single booster dose or a primary three‐dose series, depending on the hepatitis A and/or B vaccination history of subjects. Antibody responses to hepatitis A/B vaccination were assessed 1 month following the last hepatitis A and/or B dose. Serum bactericidal activity with human complement (hSBA) against meningococcal serogroups A, C, W‐135, and Y was assessed 1 month post‐MenACWY‐CRM vaccination. Safety was monitored throughout the study. Results At 1 month following the final hepatitis A and/or B vaccination, concomitant administration of hepatitis A/B and MenACWY‐CRM was non‐inferior to administration of hepatitis A/B alone in terms of geometric mean concentrations of antibodies against the hepatitis A and B antigens. One month post‐MenACWY‐CRM vaccination, the percentages of subjects achieving hSBA titers ≥8 for serogroups A, C, W‐135, and Y in the HepA/B+MenACWY‐CRM group (76, 87, 99, and 94%, respectively) were comparable to those in the MenACWY‐CRM group (67, 82, 96, and 88%, respectively). The percentages of subjects reporting adverse events (AEs) were similar across study groups and a majority of the reported AEs were mild to moderate in nature. There were no study vaccine‐related serious AEs. Conclusions MenACWY‐CRM can be administered concomitantly with a hepatitis A and/or B vaccine in the context of an accelerated hepatitis A and/or B immunization schedule without increasing safety concerns or compromising the immune responses to any of the vaccine antigens. [NCT01453348]